2016
DOI: 10.1007/s00520-016-3417-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life (QOL) and symptom burden (SB) in patients with breast cancer

Abstract: Patients ≤50 years old, 2-10 years post-treatment, treated with chemotherapy or SERM had increased SB and decreased QOL. Individualized interventions and programs can be developed to tailor to physical, educational, and psychosocial needs identified across the breast cancer continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(151 citation statements)
references
References 26 publications
5
136
2
8
Order By: Relevance
“…Both groups found that problems with sleep, tingling in hands/feet, pain, and pruritus were all reported in more than 20% of women. Correlates of physical symptom burden are also comparable to studies of other breast cancer cohorts and other cancer types . Our findings are also consistent with data that suggest that Latino women express greater symptom burden relative to black/women .…”
Section: Discussionsupporting
confidence: 89%
“…Both groups found that problems with sleep, tingling in hands/feet, pain, and pruritus were all reported in more than 20% of women. Correlates of physical symptom burden are also comparable to studies of other breast cancer cohorts and other cancer types . Our findings are also consistent with data that suggest that Latino women express greater symptom burden relative to black/women .…”
Section: Discussionsupporting
confidence: 89%
“…QOL degradation following breast cancer diagnosis occurs across 4 broad domains: functional, physical, social, and emotional wellbeing . Women diagnosed with breast cancer often contend with a constellation of physical, neurological, and psychosocial sequelae that are highly variable in terms of severity and duration …”
Section: Introductionmentioning
confidence: 99%
“…Individual characteristics (eg, age, income) and clinical factors (eg, cancer stage, time since diagnosis) contribute to survivors' QOL . A common complaint, chronic pain, is reported by up to 78% of survivors, and thought to be related to poor QOL outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for BC is divided into local‐regional, such as surgery and radiotherapy, and systemic, such as chemotherapy and hormonal therapy . The indication of treatment should be based on the stage of the disease and individual characteristics of the patient . Approximately 75%‐80% of cases of BC have an indication for hormonal therapy, which is considered active transition care for survivors .…”
Section: Introductionmentioning
confidence: 99%